PEMBUATAN TEPUNG KOMPOSIT DARI PATI GANYONG/ GARUT DAN TEPUNG LABU KUNING SEBAGAI BAHAN BAKU FLAT NOODLE - The Production of Composite Flour from Canna/Arrowroot Starch and Pumpkin Flour as Flat Noodle Ingredient - Novita Indrianti; Nok Afifah; Enny Sholichah (Balai Riset dan Standardisasi Industri Pontianak, 2019)
Non wheat noodles like flat noodle require composite starch with high amylase content such as canna and arrowroot starch as raw material. Pumpkin flour addition is expected to increase nutrition value of the composite flour. This research aimed to characterized composite flour from canna starch or arrowroot starch and pumpkin flour as ingredient for flat noodles. Six composite flour formulations were made from a mixture of canna starch or arrowroot starch with pumpkin flour at 5%, 10%, 15% concentrations. The physicochemical properties (proximate, beta-carotene, colour analysis), functional properties (swelling power, solubility, water absorption capacity, oil absorption capacity) and pasting properties (peak, breakdown, final, setback viscosity and pasting temperature) were analyzed. The results revealed that higher concentration of pumpkin flour was significantly increasing ash, protein, fat, carbohydrate and beta carotene content. The swelling power, solubility, water and oil absorption capacity increased with high concentrations of pumpkin flour, while the lightness of composite flour decreased. The addition of pumpkin flour increased peak and breakdown viscosity but decreased setback viscosity. Canna-pumpkin composite flours at 5% of pumpkin flour was recommended as ingredient for flat noodle because it has a low swelling power, low peak viscosity, low breakdown viscosity, low final viscosity and high setback viscosity.Keywords: canna/arrowroot-pumpkin composite flour, functional properties, gelatinization profile, physicochemical propertiesABSTRAKMi non gandum seperti flat noodle membutuhkan tepung komposit pati berkadar amilosa tinggi seperti pati ganyong dan pati garut sebagai bahan baku. Penambahan tepung labu kuning diharapkan dapat meningkatkan nilai gizi pada tepung komposit sebagai bahan baku flat noodle. Tujuan penelitian ini adalah untuk mengetahui karakterisasi tepung komposit dari pati ganyong/garut dan tepung labu kuning sebagai bahan baku flat noodle. Enam formulasi tepung komposit flat noodle dibuat dari campuran pati ganyong atau pati garut dengan penambahan tepung labu kuning 5%, 10% dan 15%. Karakterisasi tepung komposit meliputi sifat fisikokimia (proksimat, beta-karoten, warna), sifat fungsional (swelling, kelarutan, kapasitas penyerapan air, kapasitas penyerapan minyak) dan profil gelatinisasi (viskositas puncak, breakdown, akhir, setback dan suhu gelatinisasi). Hasil penelitian menunjukkan kenaikan konsentrasi tepung labu kuning berpengaruh signifikan terhadap kenaikan kadar abu, protein, lemak, karbohidrat, beta karoten, swelling power, kelarutan, serta kapasitas penyerapan air dan minyak tepung komposit. Kecerahan tepung komposit menurun seiring dengan peningkatan konsentrasi tepung labu kuning. Penambahan tepung labu kuning meningkatkan viskositas puncak dan breakdown, tetapi menurunkan viskositas setback tepung komposit. Tepung komposit (ganyong-labu kuning) dengan penambahan tepung labu kuning 5% direkomendasikan sebagai bahan baku flat noodle karena memiliki swelling power rendah, viskositas puncak rendah, breakdown rendah, viskositas akhir rendah dan setback tinggi. Kata kunci: profil gelatinisasi, sifat fisikokimia, sifat fungsional, tepung komposit ganyong/garut-labu kuning